Enhanced electrochemical performance of MoS2/graphene nanosheet nanocomposites. Issue 32 (19th May 2020) - Choi, Jin-Hyeok; Kim, Min-Cheol; Moon, Sang-Hyun; Kim, Hyeona; Kim, Yo-Seob; Park, Kyung-Won
Abstract : MoS2 /GNS 8 : 2 with an appropriate portion of GNS exhibited the best LIB performance, due to the lowest interfacial resistance and highest Li-ion diffusivity. Abstract : Molybdenum disulfide (MoS2 ) is attractive as an anode material for next-generation batteries, because of its layered structure being favorable for the insertion/deinsertion of Li + ions, and its fairly high theoretical capacity. However, since the MoS2 anode material has exhibited disadvantages, such as low electrical conductivity and poor cycling stability, to improve the electrochemical performance of MoS2 in this study, a nanocomposite structure consisting of MoS2 and GNS (MoS2 /GNS) as an anode for LIBs was prepared, by controlling the weight ratios of MoS2 /GNS. The X-ray diffraction patterns and electron microscopic analysis showed that the nanocomposite electrode structure consisted of well-formed MoS2 nanoparticles and GNS. Compared to MoS2 -only, the MoS2 /GNS composites exhibited high retention and improved capacity at high current densities. In particular, among these nanocomposite samples, MoS2 /GNS(8 : 2) with an appropriate portion of GNS exhibited the best LIB performance, due to the lowest interfacial resistance and highest Li-ion diffusivity.